Avaliação da dosagem de nutrientes em sistema de lagoa aerada facultativa tratando efluente kraft - Pazda, Ana Paula (2022)
All over the world the kraft process is the most used for the production of pulp and paper. In average it generates 60 m3 of effluent per ton of cellulose and contains organic matter, color and various recalcitrant compounds. Biological treatments are the most used in the pulp and paper industry. The aerated facultative lagoon (AFL) is widely used, where the group of microorganisms act in the removal of biodegradable compounds. For a good performance of the biological treatment, an adequate C↑P ratio is necessary. Therefore, nitrogen supplementation by the addition of urea and phosphorus by the addition of potassium phosphate are common practices in this sector. The aim of this study was to evaluate the effects of nutrient dosage on the performance of an AFL treating kraft pulp effluent. The performance of a laboratory scale AFL treating real effluent from the kraft pulp industry was monitored for the following ratios C↑P: 100:0.7:0.3 (Stage I), 100:0.7 :0.1 (Stage II) and 100:0.5:0.1 (Stage III). The organic load rate (OLR) was 0.2 kg COD (chemical oxygen demand).m-3.d-1 in all steps and in addition to the efficiency in removing the biochemical oxygen demand (BOD5) and COD, also followed by total organic carbon (TOC), color, total phenolic compounds (TPC) and lignin-derived compounds were also monitored. The removal of organic matter in terms of BOD5, COD and TOC among all stages were on average 80%, 40% and 40%, respectively. For the color, there was a decrease on the average of 8% in Stages I and II and in Stage III there was no color removal. The TPC had an average decrease of 7% in the different stages. No significant differences were observed in the removal of COD and BOD5 parameters, due to phosphorus (Stage II) or nitrogen (Stage III) decrease. The reduction in P content in the C↑P ratio from 100:0.7:0.3 to 100:0.7:0.1, affects the TPC and total nitrogen (TN) decrease parameters. In Stage III, when the N reduction occurred, changing the C↑P ratio from 100:0.7:0.1 to 100:0.5:0.1, most parameters showed lower removal, compared to two previous steps, but without significant difference between them. Based on the removal efficiency of the parameters in the cellulose and kraft effluent, evaluated through the treatment in the AFL system with different C↑P ratios, it can be inferred that the proportion of nutrients may be lower than that currently used by the industry that provided the samples for research without impacts on compliance with environmental legislation. The C↑P ratio used that showed the best global performance for most of the parameters evaluated was 100:0.7:0.1 corresponding to Stage II.